2020
DOI: 10.3177/jnsv.66.s190
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of Yellow Alkaline Noodles with Wheat Bran and the Impact on Physical and Sensorial Properties

Abstract: Food fortification is a commonly-used method to increase nutritional value of food products in order to reduce the risks of Non-Communicable Diseases (NCDs). Noodles are a versatile and popular staple food, especially in Asia, that can be nutritionally enriched using various types of ingredients and one of them is wheat bran that is rich in dietary fiber. This study aimed to determine effect of fortification of fresh yellow alkaline noodles with wheat bran on its physical and sensorial properties. Addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This might be due to the action of polyphenol oxidase enzyme in wheat bran that was exposed during the mixing and cooking processes. So, a rapid oxidation reaction occurs which leads to the darkening colour of pasta samples containing untreated wheat bran (Wardhana & Banawi, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the action of polyphenol oxidase enzyme in wheat bran that was exposed during the mixing and cooking processes. So, a rapid oxidation reaction occurs which leads to the darkening colour of pasta samples containing untreated wheat bran (Wardhana & Banawi, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The L value of bran-fortified stewing noodles gradually decreased with increased wheat gluten content, while the b* and ΔE values gradually increased. The decrease in the L value was attributed to the increase in protein content in noodles with the increase in gluten content, which made the gluten network structure denser and reduced the reflected light (Wardhana & Banawi, 2020). A comprehensive analysis of the effects of wheat gluten on the tensile properties, color, and sensory score of bran-fortified stewing noodles showed that the noodles were of high quality when the wheat gluten content was 10%.…”
Section: Effect Of Wheat Gluten Glucose Oxidase and Guar Gum On The C...mentioning
confidence: 99%